2018
DOI: 10.1080/00220388.2017.1417584
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Social Capital, and Grassroots Development: Insights from Rural Bangladesh

Abstract: This article examines the relationship between social capital and the creation and exchange of knowledge for grassroots development. It applies a framework that originated in developed countries to the experimental phase of a successful entrepreneurial development programme, undertaken between 2006 and 2012 in rural Bangladesh. Although generally applicable, the framework's structural dimensions are further developed and divided into three functional subtypes of social capital (bonding, bridging and linking) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Based on the aspects of social capital discussed in the conceptual framework and the findings of the recent literature review (Kiwanuka et al, 2020) and other relevant literature, a questionnaire survey was developed on the online survey platform, SurveyMonkey, to examine the role of the private sector in international development from the perspective of other sectors, namely the public sector and civil society, but also of the private sector itself. We have taken this approach because we would like to build on the existing literature but also to integrate the concept of social capital which has been demonstrated in previous studies to play an important role in knowledge brokering (see, for example, Nahapiet and Ghoshal, 1998; Cummings et al, 2019a). The link between the aspects of social capital, findings of the literature, and specific questions in the questionnaire can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the aspects of social capital discussed in the conceptual framework and the findings of the recent literature review (Kiwanuka et al, 2020) and other relevant literature, a questionnaire survey was developed on the online survey platform, SurveyMonkey, to examine the role of the private sector in international development from the perspective of other sectors, namely the public sector and civil society, but also of the private sector itself. We have taken this approach because we would like to build on the existing literature but also to integrate the concept of social capital which has been demonstrated in previous studies to play an important role in knowledge brokering (see, for example, Nahapiet and Ghoshal, 1998; Cummings et al, 2019a). The link between the aspects of social capital, findings of the literature, and specific questions in the questionnaire can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In organizational and management sciences, Nahapiet and Ghoshal (1998) have used the conceptual framework of social capital to examine the role of relational, cognitive and structural aspects of social capital in knowledge co-creation and exchange in firms. This framework has, for example, also been applied to knowledge processes at the grassroots in Bangladesh (Cummings et al, 2019a). In the latter study, gift exchange and trust were found to be more important in a grassroots setting than in firms in developed countries.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Network theory and practice indicates that epistemic network justice would involve not only access to peers but also to other actors at the boundary of networks, providing access to social capital. Social capital has been argued by many others as playing an important role in knowledge sharing and networks in many different national contexts, including in LMICs (Cummings et al, 2019). and the potentially epistemically exclusionary dimension of language' (Catala, 2022, p. 9); concrete measures to prevent or counteract linguistic epistemic injustice, such as support to non-native speakers;…”
Section: Structural Epistemic Justicementioning
confidence: 99%
“…This emphasis points towards an implicit assumption that the situation of women's entrepreneurship in urban high-income countries is the norm and that the framework is universally applicable. This begs the question raised by Cummings et al. (2019, p. 162) when interrogating the potential, universal relevance of Nahapiet and Ghoshal's (1998) framework on the relationship between social capital and intellectual capital in organizations, namely whether it is relevant to poor women subject to social constraints.…”
Section: The Grand Narrativementioning
confidence: 99%